Strength of joints and physical performance of chairs made from LVL oil palm / Abdul Hamid Saleh - Saleh, Abdul Hamid (2005)
Rubberwood has been the main raw material in furniture making after a series of research in the 80’s showed it had the potential to be used as a basic material for wooden furniture. However, as the continuous supply of rubberwood is not possible to sustain the industry, research on the use of oil palm timber were initiated to determine the applicability of this material as an alternative. This study used oil palm and rubberwood veneer in the form of laminated veneer lumber (LVL). The LVL’s oil palm board was pressed based on pressures applied to rubberwood LVL board using a high frequency press machine. The studies investigated the specific gravity, MOE and MOR, strength of T-shape joints and physical performance of a particular item of furniture, the JUNO chair. The results of specific gravity showed the value of rubberwood LVL was 0.7642 whilst the value of oil palm LVL was 0.5549, which is significantly different. The values of MOE and MOR between rubberwood and oil palm LVL were significantly different. Meanwhile the T-shape joints for three types of tests; namely, end-to-edge, end-to-surface and edge-to-surface mostly showed not significant difference. Results of the physical performance test on LVL oil palm JUNO chair fulfilled the requirements of BS 4875 part 1, 1985. However, there was a minimum failure (crack and split) at the end of legs. Indeed, the strength properties of oil palm LVL were comparable to those of rubberwood LVL that was affected with one parameter of pressure in this study.